Erosion-Resistant Electrode Coatings of Vacuum and Gas-Discharge Switching Devices. Issue 17 (2016) - Karabanov, Sergey; Suvorov, Dmitry; Gololobov, Gennady; Gurov, Victor; Slivkin, Evgeny; Tarabrin, Dmitry
ABSTRACT: The paper presents the results of numerical modeling of thermomechanical stresses and thermal fields for conditions of erosion-resistant electrode coatings of vacuum and gas discharge switching devices with W-Ti-Cu and W-Mo-Cu structures at local temperature and electric current influence in axially symmetrical approximation. The efficiency assessment of intermediate layers introduction by comparison of interlaminar mechanical stresses is carried out. It is shown that introduction of titanium interlayer in the coating with W Cu structure results in considerable (more than two times) decrease of internal thermomechanical stresses between layers that increases coating resistance to delamination. The optimum value of interlayer thickness at which the minimum thermomechanical stresses are provided is determined.